Shizuko Yoshikawa - Schaad, Gabrielle 1982- (Lars Müller Publishers, 2018)
"Shizuko Yoshikawa (born 1934 in Japan, based in Switzerland) was one of the first and few Japanese students at the Ulm Hochschule fur Gestaltung, known as the postwar "Bauhaus." She later married the renowned designer Josef Muller-Brockmann (1914-1996), a pioneer of Swiss Graphic Design, and moved to Switzerland, where she became an artist and a member of the second generation of concrete art. Amongst the very few women belonging to this art movement, she takes a special position due to her Japanese origins and education. Her work combines the rational concepts of European modern art with the poetry and ease of the intuitional Japanese Zen tradition. This first monograph on Shizuko Yoshikawa s work contains a major essays by art historian Gabrielle Schaad and an contribution by Prof. Midori Yoshimoto, highlighting the life of the artist and interpreting her oeuvre in the Japanese context. Inspired by this publication, an exhibition will take place in Tokyo and Zurich in 2018."
This publication is initiated by the Shizuko Yoshikawa and Josef Müller-Brockmann Foundation and generously supported by the Swiss Arts Council Pro Helvetia and the Canton of Zurich
Keywords: Yoshikawa, Shizuko -- 1934-2019; Frauen in der Kunst; Kulturaustausch Schweiz und Japan; konstruktiv-konkrete Kunst; Bildband